Pengembangan Edible Dual-Indicator Sensor Ekstrak Bunga Telang dan Kunyit untuk Monitoring Kesegaran Kerang Darah - Cindy Fachriza Ulfa (Fakultas Farmasi, 2026)
Blood clams (Anadara granosa) are highly perishable seafood products, often making it difficult for consumers to assess their freshness in sealed packaging. Conventional synthetic indicators pose safety risks, necessitating the development of safe, natural alternatives. This research aims to develop an edible dual-indicator sensor using butterfly pea flower (Clitoria ternatea L.) and turmeric (Curcuma longa) extracts immobilized on a bacterial cellulose (nata de coco) membrane to monitor blood clam freshness. This laboratory-experimental study determined optimum fabrication conditions, characterized the membrane using SEM and FTIR, and evaluated sensor performance parameters including response time, reproducibility, and shelf life. The results showed that the optimum fabrication conditions were achieved using 1% butterfly pea extract with 1.5% PVA and 0.5% turmeric extract with 0.2% PVA. Characterization revealed successful immobilization through hydrogen bonding and stable pore distribution. The sensors exhibited rapid response times of 4 minutes for butterfly pea and 3 minutes for turmeric, high reproducibility (RSD < 5%), and a shelf life of 14-18 days depending on storage temperature. Application on blood clams showed significant color transitions correlating with spoilage parameters; the butterfly pea indicator changed from grayish-blue to cyan, while the turmeric indicator shifted from bright yellow to brownish-yellow. Spoilage occurred after 8 hours at room temperature, marked by a log total microbial count of 6.459 CFU/g and TVB-N levels exceeding 30 mg/100g, both clearly detected by the sensor color changes. In conclusion, the edible dual-indicator sensor is an effective, safe, and reliable tool for real-time monitoring of blood clam freshness.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: Edible Sensor; Blood Clams; Butterfly Pea; Turmeric; Smart Packaging